Pemahaman dan pengalaman guru Pendidikan Islam menerapkan elemen amalan dalam pengajaran - Mohd Fakhruddin, Fathiyah; Alwi, Nor Hayati; Hamzah, Azimi; Abdul Mutalib, Lukman (Faculty of Education, University of Malaya, 2013)
This study discusses the Islamic education?s teachers? understanding and experience in inculcating the deed (ibadah) element in their teaching practices. This study employed the qualitative approach. In-depth interview, observation and document analysis were conducted for the data collection purpose. The result shows that teachers? understanding of the said element refers to the concept of worship that needs to be performed in line with the ?shariah? and needs to be practiced in our daily life. Meanwhile, teachers? experience in inculcating the ?ibadah? element is done through demonstrations, consistent practices, monitoring, advising and highlighting the significance of the ?ibadah?. In conclusion, this study illustrates that the ?ibadah? element is well-understood and applied by the teachers. However, some aspects may need to be improved. Finally, this study also discusses the implications and suggestions for future research.